Ownership Rights to Buildings that Stand on Water - Muhammad Tri Mulya Putra; Resiani Corry Djara Liwe; Artha Marina Yonathan Behar; Gianto Umbu Ngailu Deddi (Journal Equity of Law and Governance, 2024)
Floating houses, or "Rumah Terapung," are unique residential concepts built on water rather than on land. This tradition, deeply rooted in Indonesian coastal communities, involves constructing homes on lakes, rivers, marshes, and coastal areas, reflecting a lifestyle passed down through generations. Indonesian law, particularly Law No. 28 of 2002 concerning Buildings, permits the construction of structures above or below land, water, or public infrastructure, which must be registered with the government to ensure proper use and development. However, many floating houses remain unregistered due to unclear land rights. The National Land Agency (BPN) oversees the registration of land rights, including maritime cadastres, which are essential for managing coastal and marine areas. Despite Indonesia's abundant coastal resources, the country lacks a dedicated maritime cadastre organization, necessitating the development of appropriate measurement, mapping, and rights registration processes to provide legal certainty for these water-based structures. The guarantee of immovable objects like floating houses involves Mortgage Rights under Law No. 4 of 1996. The principle of horizontal separation in Indonesian land law, which distinguishes ownership of land and buildings, complicates the registration and guarantee process. Government authority encompasses various laws and regulations, including Law No. 11 of 2020 and Law No. 26 of 2007, requiring coordination between central and regional governments in planning, licensing, environmental assessment (AMDAL), supervision, law enforcement, and conservation. Proper coordination ensures sustainable and environmentally friendly development, preserving Indonesia's coastal and marine resources. Clear regulations and processes are essential to provide legal certainty and support the sustainable development of floating housing settlements, ensuring that these unique communities continue to thrive.